Term Lowbirth Weight Neonate: Maternal Factors (Medico Legal Update, 2021)
The current research aims to detect the maternal risk factors that influence the birth weight of the babies.Risk factors related to the mothers like gestational age, maternal age, nutrition, and medical problems playa role in the delivery of infants with low birth weight. The sample consisted of 267 ladies give a birth tonewborns. Mothers with less than or = 150cm giving low birth weight babies (62.3%) while those with morethan 150cm giving low birth weight babies (37.7%) . In the normal birth weight group, working mothersrepresent (82.1%) while in normal birth weight group they represent (17.4%). Mothers more than or = 35years old giving (33.1%) normal birth weight babies. Young mothers less than 20 years old gave more lowbirth weight babies (28.7%) than older mothers with more 20 years old.The maternal risk factors of low birth weight babies include maternal age < 20 years old, low maternaleducational level, working mothers, smoking, pre-pregnancy weight